Challenges in the ethics review process of clinical scientific research projects in China. Issue 10 (October 2019) - Wang, Zhu-Heng; Zhou, Guan-Hua; Sun, Li-Ping; Gang, Jun
Purpose: Ethics review processes have become increasingly complex. The objective of this study was to explore the challenges currently faced in ethics reviews of clinical scientific research projects in China, with the goal of standardizing the structure of medical ethics committees and better protecting the rights and interests of research participants. Methods: We reviewed and comprehensively analyzed the available literature discussing standardized ethics reviews of clinical scientific research projects. Results: We identified the following problems: incomplete legislation, absence of supervision, vague review criteria, limitations of ethics committee competence, inadequate ethics consciousness, and poor tracking of reviews. In this paper, we suggest strategies for the development of future ethical reviews of clinical scientific research projects. Conclusion: To standardize the ethics review process of clinical scientific research projects in China, it is necessary to establish relevant laws and regulations and implement supervisory responsibilities. Professional training of medical ethics committees is suggested as an effective way to improve the quality of ethics reviews.